Shortened Fingers and Toes: GNAS Abnormalities are Not the Only Cause - Reyes, Monica (Exp Clin Endocrinol Diabetes, 2019)
The PTH/PTHrP receptor (PTHR1) mediates the actions of parathyroid hormone (PTH) and PTH-related peptide (PTHrP) by coupling this G protein-coupled receptor (GPCR) to the alpha-subunit of the heterotrimeric stimulatory G protein (Gsα) and thereby to the formation of cAMP. In growth plates, PTHrP-dependent activation of the cAMP/PKA second messenger pathway prevents the premature differentiation of chondrocytes into hypertrophic cells resulting in delayed growth plate closure. Heterozygous mutations in GNAS, the gene encoding Gsα, lead to a reduction in cAMP levels in growth plate chondrocytes that is sufficient to cause shortening of metacarpals and/or -tarsals, i. e. typical skeletal aspects of Albright’s Hereditary Osteodystrophy (AHO). However, heterozygous mutations in other genes, including those encoding PTHrP, PRKAR1A, PDE4D, and PDE3A, can lead to similar or even more pronounced acceleration of skeletal maturation that is particularly obvious in hands and feet, and reduces final adult height. Genetic mutations other than those resulting in Gsα haploinsufficiency thus reduce intracellular cAMP levels in growth plate chondrocytes to a similar extent and thereby accelerate skeletal maturation.